In vitro activity of N-chlorotaurine (NCT) in combination with NH(4)Cl against Trichomonas vaginalis - Fürnkranz, Ursula (Elsevier Science Publishers, 2011)
Trichomoniasis, caused by the protozoan Trichomonas vaginalis, is usually treated with metronidazole, however resistance is on the rise. In this study, N-chlorotaurine (NCT), a new endogenous mild active chlorine compound for topical use, killed T. vaginalis in vitro within 15 min of treatment at a concentration of 55 mM (1%), which is well tolerated by human tissue. The activity of NCT was further enhanced by addition of ammonium chloride (NH(4)Cl). A combination of 5.5 mM (0.1%) NCT plus 19 mM (0.1%) NH(4)Cl killed 100% of trichomonads within 5 min.